2020
DOI: 10.5897/ajar2020.14950
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing maize production in a Striga infested environment through weed management practices, sowing date and improved crop varieties

Abstract: A two-year investigation into the effects of weed management practices, sowing dates and maize varieties was made in a Striga endemic field at Minna, Nigeria. The treatment was a factorial combination of variety (SAMMAZ 15, 17, 37, 40 and SUWAN-1-SR-Y), weed management practices (weedy check, two hoe weeding (HW) at 3 + 6 weeks after sowing (WAS), pre-emergence (PE) Atrazine at 2.4 kg a.i ha-1 + 1 HW at 6 WAS and PE Atrazine at 2.4 kg ha-1 + post-emergence (POE) Nicosulfuron at 0.06 kg ha-1 at 6 WAS) and sowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The highest grain yield of sorghum due to relay-intercropping could be due to complementarity between sorghum and chickpea. This idea is agreed with the finding of Aliyu and Emechebe (2006) [2] who revealed that higher grain yield may be attributed to the effectiveness of cropping system. Another reason for this also could be due to efficiently use of growth resources and conversion ability to the grain yield.…”
Section: Grain Yield (Tha -1 )supporting
confidence: 92%
“…The highest grain yield of sorghum due to relay-intercropping could be due to complementarity between sorghum and chickpea. This idea is agreed with the finding of Aliyu and Emechebe (2006) [2] who revealed that higher grain yield may be attributed to the effectiveness of cropping system. Another reason for this also could be due to efficiently use of growth resources and conversion ability to the grain yield.…”
Section: Grain Yield (Tha -1 )supporting
confidence: 92%
“…This superior CP concentration in Perkins' PM+MB mixture reinforced Horn et al ( 2020) assumption that N fixation by mung beans enhanced soil N availability for pearl millet development in N-deficient soils (like Perkins). Other studies also reported that planting legumes with pearl millet improved grass crop development in N-limiting environments in Africa (Gbèhounou & Adango, 2003;Aliyu & Emechebe, 2006).…”
Section: Discussionmentioning
confidence: 93%